Interview with Nancy Campbell. Issue 4 (2nd October 2018) - Youngs, Tim
ABSTRACT: In an interview conducted on 29 November 2018 at Nottingham Trent University and followed up by email on 29 March 2019, Nancy Campbell talks to Tim Youngs about her book The Library of Ice (2018). The book is a cultural history of ice, which draws on Campbell's experience of travel in the Arctic and elsewhere since 2010, and brings to a close several years of publishing projects on the region. Campbell discusses the relationship between travel, science and literature in her work, describing her method as being like a journey through ideas supported by experience of place. She explains her lack of interest in offering an inner journey, being more concerned to explore people's relationship to their environment, including their creative responses to it, and in particular those inhabitants of the North whose lives are affected by climate change.